Completeness of pharmaceutical industry insulin adverse event reports from Africa and the Middle East. Issue 3 (4th March 2023) - Mlotshwa, Charity RN; Burger, Johanita R.; Vorster, Martine; Rakumakoe, Dorcas M.; Cockeran, Marike
ABSTRACT: Background: Growing numbers of patients with diabetes mellitus in Africa and the Middle East on antidiabetic therapies necessitate understanding adverse event reporting in these regions. We assessed pharmaceutical industry insulin individual case safety report (ICSR) completeness and completeness-associated variables. Research design and methods: The observational cross-sectional study, set in an insulin-manufacturing company's safety database, assessed vigiGrade® completeness scores of African and Middle Eastern post-marketing ICSRs from January to December 2018, and case variables effects on completeness. Low vigiGrade® scores indicated poorly documented ICSRs. Results: We analyzed 4854 ICSRs; 59.8% from the Middle East. The mean vigiGrade® score was 0.58. Middle Eastern ICSRs had higher mean scores than African ICSRs (0.65 vs. 0.46, p<0.001). Scores peaked at 0.32, 0.70, and 1.00 for Middle Eastern ICSRs compared to 0.35 and 0.50 for African ICSRs. Middle Eastern serious (0.77 vs. 0.47; p<0.001) and solicited (0.70 vs. 0.48; p<0.001) ICSRs had higher mean scores than African ICSRs. Mean scores were highest for Middle Eastern physicians (0.89) and other healthcare professionals (0.82), whereas, in Africa, scores were highest for consumer- (0.47) and pharmacist-reported ICSRs (0.47) (p<0.001). Conclusions: Middle Eastern pharmaceutical industry insulin ICSRs were documented with greater detail than African ICSRs. Seriousness, report source, and reporter type significantly impacted ICSR completeness.